Psychic school wars [videorecording (Blu-Ray)] - Nakamura, Ryosuke; Watanabe, Mayu; Honjo, Yutaro; Hanazawa, Kana, 1989-; Mayumura, Taku, 1934-2019 (FUNimation, 2016)
Spring marks the start of another new school year at a junior high school in Kamakura. A new transfer student, Ryoichi Kyogoku joins the 8th grade. Kyogoku has a very special proficiency in telepathy and has been ordered by his father to use this ability to scan other people's minds and take over the school. He instantly gains popularity from his good looks and charisma and he sets about taking control. As people begin to fall under Kyogoku's spell, he covertly manipulates his followers and pushes aside anyone who gets in his way. With the school almost completely under the control of Kyogoku, only one boy seems unaffected-Seki. Does Seki have what it takes to save everyone from the clutches of mind control?